Sri Ramakrishna for you:selected teachings and conversations of and thoughts and writings on Sri Ramakrishna Paramahansa Deva - Roychowdhury (Deep Prakashan, 2015)
Sri Ramakrishna for you:selected teachings and conversations of and thoughts and writings on Sri Ramakrishna Paramahansa Deva / Roychowdhury; Satyam (ed.). -- Kolkata: Deep Prakashan, 2015 181.4 R165 No. of Copies : 2